Association of IL‐17A‐197G/A and IL‐17F‐7488T/C polymorphisms and osteoarthritis susceptibility: A meta‐analysis. (31st October 2019) - Gao, Shutao; Mao, Chao; Cheng, Jie; Deng, Qiang; Sheng, Weibin
Abstract: Aim: This meta‐analysis was conducted with the aim of collecting and synthesizing the existing evidence on the association of interleukin‐17A ( IL‐17A ) ‐197G/A and IL‐17F‐7488T/C gene polymorphisms and osteoarthritis (OA) susceptibility. Methods: Six electronic databases including PubMed, EMBASE, Web of Science, Cochrane Library, CNKI, and Wanfang were systematically searched for potentially relevant studies previous to June 2019. The strengths of association were estimated by summary odds ratios (ORs) and 95% confidence intervals (95%CIs) in a model‐free approach. Heterogeneity test and sensitivity analysis were also conducted to guarantee the reliability of this study. Results: Six eligible case‐control studies comprising 1989 OA patients and 2116 healthy controls were obtained for the meta‐analysis. Dominant model was confirmed to be the optimal genetic model (MM + Mm vs mm). The pooled estimate supported that IL‐17A‐197G/A and IL‐17F‐7488T/C polymorphisms were significantly associated with OA susceptibility in the overall population ( IL‐17A‐197G/A : GG + GA vs AA, OR = 0.69, 95%CI 0.57‐0.80; P < .001; IL‐17F‐7488T/C, TT + TC vs CC, OR = 0.46, 95%CI 0.29‐0.71, P < .001). However, subgroup analyses suggested the association only existed in Asians and knee OA. Conclusion: The findings of the present study indicate that IL‐17A‐197G/A and IL‐17F‐7488T/C polymorphisms are positively associated to reduced risk of knee OA, especially in Asian populations.